One-Dimensional Computation Method of Supercritical CO2 Labyrinth Seal - Yuming Zhu; Yuyan Jiang; Shiqiang Liang; Chaohong Guo; Yongxian Guo; Haofei Cai (Applied Sciences, 2020)
An actual one-dimensional(1-D) computation method for a labyrinth seal is proposed. Relevant computation hypotheses for the 1-D method are analyzed and the specificity of internal flow in an SCO2 (supercritical CO2) labyrinth seal is explored in advance. Then, the experimental correlation discharge coefficient and the residual kinetic energy coefficient used in SCO2 labyrinth seals are proposed. In addition, the speed of sound in two-phase flow is corrected in the 1-D method. All recent experimental results of the SCO2 labyrinth seal are sorted out and the latest experimental results of a stepped-staggered labyrinth seal are proposed to verify the accuracy and applicability of the 1-D method. Finally, the sealing efficiency of the SCO2 labyrinth seals are analyzed using the 1-D method.